MORPHOGENESIS OF THE MINOR SALIVARY GLANDS OF THE HARD PALATE DURING TRIPTORELIN ADMINISTRATION IN THE EARLY OBSERVATIONAL TERMS IN RATS - Shepitko, V.I.; Stetsuk, Ye.V.; Shtepa, K.V.; Boruta, N.V.; Voloshyna, O.V.; Pelipenko, L.B.; Serbin, S.I. (World of Medicine and Biology, 2023)
Minor salivary glands are very sensitive to pathological processes in the body. However, until now, the reactivity of minor salivary glands in response to neuroendocrine changes in the body has not been sufficiently studied and is, therefore, one of the unsolved problems of modern morphology. Triptorelin administration has a negative effect on the structural components of the secretory and excretory ducts of the minor salivary glands of rats. They were manifested by a statistically significant increase in all structural elements with a maximum on the 30th day, without restoring them to the indicators of the control group on the 180th. Comparing the morphometric indicators of the experimental group on the 30th and 180th days, a statistically significant decrease in morphometric indicators was determined. Mucous cell height decreased by 21 %, the outer diameter of the terminal secretory unit – by 22 %, the lumen of the terminal secretory unit – by 27 %; the height of the principal cells of the excretory ducts – by 9 %, the outer diameter of the excretory ducts – by 24 %, the lumen of the excretory ducts – by 27 %. In our opinion, this happened due to decreased compensatory properties of the tissues of the minor salivary glands.
Keywords: triptorelin; testosterone; luteinising hormone; minor salivary glands; mucous cells; excretory ducts